Case report: Insulin desensitization as the only option for managing insulin allergy in a Sudanese patient - Said, Rihan; Goda, Rayan; Abdalrahman, Ihab B.; Erwa, Nahla H. H. (Frontiers in Allergy, 2023)
Introduction Allergic reactions to insulin have become very rare with the introduction of human insulin. Anaphylaxis is a life-threatening condition that results from immediate IgE-mediated hypersensitivity. Desensitization to human insulin was reported to control immediate hypersensitivity reactions to insulin. Here, we describe the history and challenges of managing our patient and the development of an insulin desensitization protocol in a resource-limited setup. Case Summary A 42-year-old Sudanese woman with poorly controlled type 2 diabetes on maximum antidiabetic medications required insulin therapy to achieve reasonable glycemic control. She developed progressive and severe immediate hypersensitivity reactions to insulin, including anaphylaxis. Serum sample analysis demonstrated insulin-specific IgE antibodies. The patient's poor glycemic control and the need for breast surgery indicated insulin desensitization. A 4-day desensitization protocol was delivered in an ICU bed for close observation. Following successful desensitization and 24-h observation, our patient was discharged on pre-meal human insulin, which was tolerated well to the current date Conclusions Although insulin allergy is rare, once encountered, it is very challenging in patients who have no other treatment options available. Different protocols for insulin desensitization are described in the literature; the agreed protocol was implemented successfully in our patient despite the limited resources.